(untitled) (International Journal of Engineering and Computer Science, 2018)
The motivation for every location based information system is: “To assist with the exact information, at right place in real time with personalized setup and location sensitiveness”. In this era we are dealing with palmtops and iPhones, which are going to replace the bulky desktops even for computational purposes. We have vast number of applications and usage where a person sitting in a roadside café needs to get relevant data and information. A very appealing application includes surveillance where instant information is needed to decide if the people being monitored are any real threat or an erroneous target. We have been able to create a number of different applications where we provide the user with information regarding a place he or she wants to visit. But these applications are limited to desktops only. We need to import them on mobile devices. We must ensure that a person when visiting places need not carry the travel guides with him.